2022
DOI: 10.4103/jfmpc.jfmpc_2137_21
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health problems and major risk factor profile of non communicable diseases among workers in the Aquaculture industry in Visakhapatnam

Abstract: Background: Globally the rapid growth of the aquaculture sector has generated a huge work force posing significant risks to the workers due to the combined effect of the exposure to hazards at the workplace and unhealthy lifestyle. Aim and Objectives: To study the morbidity profile of workers in the aquaculture industry in terms of the occupational health problems and risk factors of non-communicable diseases. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…weather (hot in summer, cold in winter). These precarious working conditions combined with the physically demanding nature of the job, contribute to the elevated risk of health issues; including mental disorders 14,22 . The prevalence of depression symptoms in this study is lower compared to that observed in studies involving fishermen, industrial workers and the elderly [23][24][25] .…”
Section: Nguyen Van T Et Al Depression Among Aquaculture Workers In H...mentioning
confidence: 99%
See 1 more Smart Citation
“…weather (hot in summer, cold in winter). These precarious working conditions combined with the physically demanding nature of the job, contribute to the elevated risk of health issues; including mental disorders 14,22 . The prevalence of depression symptoms in this study is lower compared to that observed in studies involving fishermen, industrial workers and the elderly [23][24][25] .…”
Section: Nguyen Van T Et Al Depression Among Aquaculture Workers In H...mentioning
confidence: 99%
“…Workers in the aquaculture sector engage in strenuous and highly specialized labor and are frequently exposed to aquatic environments and influenced by harsh weather conditions. Additionally, the occupational safety and hygiene conditions for these workers are often inadequate, posing various health risks 13,14 . Currently, global research has primarily focused on the physical health of these workers, with insufficient attention given to their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational risk factors in emerging industries: With the rapid growth of industries and changing work patterns in the Indian subcontinent, there is a need to investigate the occupational risk factors associated with new and emerging industries, such as e-commerce, information technology, and service sectors. Acknowledgment and mitigation of the potential respiratory hazards in these industries are crucial to implementing appropriate preventive measures [ 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…A community-based cross-sectional study conducted among workers in five aquaculture farms in Visakhapatnam, India, showed the prevalence of diabetes to be 9.6%. 10 Another study conducted by Ta-Chin Wang et al on 962 aquaculture workers in Taiwan showed that the prevalence of metabolic syndrome was 44.5%. 11 Labor in the aquaculture sector is hard, dangerous, and highly specific; most of the laborers are freelance workers, frequently exposed to the water environment and affected by hard weather conditions; hygienic and safe working conditions are not guaranteed, with significant risks of potential illness.…”
Section: Introductionmentioning
confidence: 98%
“…11 Labor in the aquaculture sector is hard, dangerous, and highly specific; most of the laborers are freelance workers, frequently exposed to the water environment and affected by hard weather conditions; hygienic and safe working conditions are not guaranteed, with significant risks of potential illness. 10,12 Currently, health care for aquaculture workers in Vietnam has not received adequate attention and there is scant research on the health status of this group of workers, including factors related to diabetes. Therefore, we assessed the prevalence of and some factors related to diabetes among aquaculture workers in Hai Phong, Vietnam, in 2022.…”
Section: Introductionmentioning
confidence: 99%